2023
DOI: 10.3390/ijms24021413
|View full text |Cite
|
Sign up to set email alerts
|

Is the Triggering of PD-L1 Dimerization a Potential Mechanism for Food-Derived Small Molecules in Cancer Immunotherapy? A Study by Molecular Dynamics

Abstract: Using small molecules to inhibit the PD-1/PD-L1 pathway is an important approach in cancer immunotherapy. Natural compounds such as capsaicin, zucapsaicin, 6-gingerol and curcumin have been proposed to have anticancer immunologic functions by downregulating the PD-L1 expression. PD-L1 dimerization promoted by small molecules was recently reported to be a potential mechanism to inhibit the PD-1/PD-L1 pathway. To clarify the molecular mechanism of such compounds on PD-L1 dimerization, molecular docking and molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…The result suggested that the high flexibility of A Tyr56 allowed αmangostin to interact with both forms of Tyr56 after 100 ns simulation. Molecular dynamics study of the natural bioactive compounds capsaicin, zucapsaicin, 6-gingerol, and curcumin with the PD-L1 dimer revealed that the key residues Ile54, Tyr56, Met115, and Ala121 play a role in stabilizing protein-ligand complexes [38]. This study also revealed that Tyr56, Met115, and Ala121 were key residues for ligand binding.…”
Section: Molecular Dynamics Simulationmentioning
confidence: 79%
“…The result suggested that the high flexibility of A Tyr56 allowed αmangostin to interact with both forms of Tyr56 after 100 ns simulation. Molecular dynamics study of the natural bioactive compounds capsaicin, zucapsaicin, 6-gingerol, and curcumin with the PD-L1 dimer revealed that the key residues Ile54, Tyr56, Met115, and Ala121 play a role in stabilizing protein-ligand complexes [38]. This study also revealed that Tyr56, Met115, and Ala121 were key residues for ligand binding.…”
Section: Molecular Dynamics Simulationmentioning
confidence: 79%
“…PD-L1 can form homodimers and tetramers, and its complex glycosylation is linked to the homodimeric structure of its intracellular domain [ 190 ]. Natural compounds such as capsaicin, 6-gingerol, and curcumin may block the PD-1/PD-L1 interaction by targeting PD-L1 dimerization, enhancing anticancer immunity [ 191 ]. The small molecule BMS-202, with modified carbonyl to hydroxyl groups, produces two enantiomers, MS and MR, both of which disrupt PD-L1 function by targeting its dimerization [ 192 ].…”
Section: Therapeutic Prospects and Clinical Transformation Of Pd-1/pd...mentioning
confidence: 99%
“…Su et al introduced carbon-based PROTACs (CDTACs), which also target PD-L1 but for proteasome degradation, showing promise in preclinical studies by inhibiting tumor growth and boosting the immune response [165]. Sun et al [190,191] Table 1 Targeting posttranslational modifications of PD-1/PD-L1 developed ROTACs, a type of PROTAC that targets and degrades specific signaling molecules, using a chimera called R2PD1 to efficiently degrade PD-L1 in melanoma cells, outperforming existing treatments in activating immune responses and inhibiting tumor growth [166]. These developments suggest that PROTACs could significantly improve PD-1/PD-L1-targeted therapies for cancer [167].…”
Section: Pd-1/pd-l1 Ubiquitination Treatment Prospects and Clinical T...mentioning
confidence: 99%